Emotional quotient (EQ) and leadership potential of nurses at Gat Andres Bonifacio Memorial Medical Center - Haduca, Sheryl F.
The healthcare system is undergoing unprecedented change. Advances in science are resulting in phenomenal technology making it possible for health care providers to offer better care than ever before in human history. Economics are also requiring and indeed forcing cutbacks in services at every turn. These changes forced organizations to go through radical resolutions within the century to cope with the current health care mandates. With this, comes a corresponding transformation of the emotional landscape. Everyone involved in healthcare is scrumbling to find new structures and processes that can do more for less. In this kind of environment, the need for effective leadership is highly crucial. Managerial domination of the organizational hierarchy has passed and the virtuoso of emotional competence is now the leadership trend.{{{{This study was conducted to determine the relationship between emotional intelligence and leadership potential among staff nurses in Gat Andres Bonifacio Memorial Medical Center (GABMMC). It also examined whether socio-demographic characteristics of the respondents:age, sex, marital status, educational attainment, degree of religiosity, achievements, family constellation, personality type, support availability and life events affect leadership potential.{{{{The study utilized a descriptive - correlational study design. One hundred nurses participated in the study who where currently working in a tertiary medical center in Manila. A socio-demographic questionnaire and two instruments were used to elicit the required data. The modified EQ map assessed the level of emotional intelligence of the respondents. Its consists of thirty - item Likert type category with four response alternatives: very well, moderatley well, a little and not at all. Leadership questionnaire measured leadership potential in terms of decision, conviction, conflict, temper, humor and energetic enthusiasm. The tools were both pre-tested and validated through reliability coefficient. Analysis of data was accomplished through the use of descriptive and inferential statistics.{{{{Results indicate that emotional quotient is correlated with leadership potential. A positive moderate statistically significant correlation (r=0.625) was demonstrated at 0.01 level of significance. This soundly imply that emotional quotient goes in the same direction with leadership potential. The higher EQ a nurse has, the greater his or her leadership potential. It therefore strongly suggests that emotionally intelligent individuals have the greater edge to take leadership positions.}}}Another interesting finding is perhaps the relative influence of age, sex, and life events on leadership potential. These variables were found to play a cogent role in influencing leadership potential due to their significant statistical association. Being women, being mature ...